Estudio de factibilidad para la creación de una academia particular de futbol, para niños y adolescentes en la ciudad de Loja. - Ambrosi Zambrano, Vicente Paul (2010)
The reason for which we wanted to make this theme, it is because there is a need in our city of an Academy to provide a positive alternative to children and adolescents to enter the football field. The training aims to achieve a capable conditioning, allowing the athlete to deal successfully with the rigors of competition. To achieve these goals and the foundations technicians - tactical, requires a correct physical preparation so balanced according to the needs of each group. Within the physical preparation should include certain Athletic Foundation enabling the footballer to move in the field quickly and fluently with relaxed and synchronized movements that do not involve an excessive energy consumption, getting better average rate base is considered larger displacement is achieved in the unit of time, are characterized by very rapid, explosive movements and large mirroring that considered in football, are movements the athlete must perform to arrive in time to receive the ball pass and is crucial to develop a backlash. Best physical condition enables you to fill in cases the lack of perfection techniques, this should work properly for an explosive muscle strength, athletic - tactical and physical - technical aspects, should be mutually supportive and achieve a common goal. An athlete with great talent but no good physical fitness is not conceived to address the requirements of the high competition. A great sprinter without knowledge of football is not accepted. You must search for virtues and exploit them looking for useful reason for which a computer should be divided but supplemented functions. But the efforts of each must be committed to each other in order to achieve a harmony and positive results. Generally referring to the characteristics of the work in specific effort of developing sportsman best conditions in its athletic State, so we have: Expressed and developed with repetition, movement speed implementation and reaction Force developed muscles, primarily in the members below. Skill, using repetitions with coordinated to develop the speed and the high frequency of movements Amplitude cycles of movements, both in whose displacement must be fast, vigorous, arms and legs relaxed. Energetic push forward, always forward. Really need much preparation and our Academy aims to train elite players to be professional players. For this reason we believed convenient to make this investment project to determine whether there is feasible to do the same within our city. To the study of market, I was in the city of Loja, there are some colleges‟ footballs but not adequate infrastructure or trained coaches, etc. That is why our Academy CUMAM SOCCER provides great expectations for the structural and educational organization in the training of children and adolescents in the city of Loja. The implementation of the project requires an investment of $ 8322,31; which will be financed by the two partners follows, half by Mr. Paul Ambrosi is $ 4161,15 and the other half by Mr. Geovanny Cumbicus is $ 4161,15 To determine the budget of income determined more than 200 students in the month, with a monthly fee of $ 20 per month per pupil, with a margin of 40% utility Has verified that the project is economically profitable based on levels of financial evaluation As projections we obtain a VAN of $ 8856,67 indicating that it is feasible to carry out the project. La Relation benefit/cost is 1.40 indicates that for each dollar invested there will be a utility of 0.40 cents. The TIR, gave us a result than the rate of 63,65% capital which makes the investment cost. Recovery of the capital will be in 3 years, 2 months and 5 days. Universidad Nacional de Loja The sensitivity analysis gave us conclusion, that the project is cost-effective, since it is not affected increases in costs and decrease in income, since its coefficient is less than